Infant formula feeding practices and the role of advice and support: an exploratory qualitative study - Jessica Appleton; Rachel Laws; Catherine Georgina Russell; Cathrine Fowler; Karen J. Campbell; Elizabeth Denney-Wilson (BMC, 2018)
Abstract Background Infant formula feeding practices are an important consideration for obesity prevention. An infant's diet is influential on their later risk of developing overweight or obesity, yet very little is known about infant formula feeding practices. It is plausible that certain modifiable practices may put children at higher risk of developing overweight or obesity, for example how much and how often a baby is fed. Understanding how parents use infant formula and what factors may influence this practice is therefore important. Moreover, parents who feed their infants formula have identified a lack of support and access to resources to guide them. Therefore this study aimed to explore parents' infant formula feeding practices to understand how parents use infant formula and what factors may influence this practice. Methods Using an explorative qualitative design, data were collected using semi-structured telephone interviews and analysed using a pragmatic inductive approach to thematic analysis. Results A total of 24 mothers from across Australia were interviewed. Mothers are influenced by a number of factors in relation to their infant formula feeding practice. These factors include information on the formula tin and marketing from formula manufacturers, particularly in relation to choosing the type of formula. Their formula feeding practices are also influenced by their interpretation of infant cues, and the amount of formula in the bottle. Many mothers would like more information to aid their practices but barriers exist to accessing health professional advice and support, so mothers may rely on informal sources. Some women reported that the social environment surrounding infant feeding wherein breastfeeding is promoted as the best option leads a feeling of stigma when formula feeding. Conclusions Additional support for parents' feeding their infants with formula is necessary. Health professionals and policy around infant formula use should include how formula information may be provided to parents who use formula in ways that do not undermine breastfeeding promotion. Further observational research should seek to understand the interaction between advice, interpretation of cues and the amount formula fed to infants.